EXPLORING THE ROLE OF TRADITIONAL BONE SETTERS: A CULTURAL STUDY AMONG THE SUMI TRIBE OF NAGALAND - Awomi, Vinisheli; Lone, Ahrar Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Traditional bone setting is one of the most common forms of traditional medicine practiced among the Sumi Nagas. This study explores the traditional bone-setting practice, cultural significance, and efficacy in the local healthcare landscape. This study was conducted using a semi-structured interview schedule. Traditional bone setters, local citizens and medical professionals were interviewed for this study. Purposive and snowball sampling were employed to recruit the participants. Field notes and audio recordings were transcribed, and the data was analysed using thematic analysis. We have examined the skills of traditional bone setters, the type of injuries they treat, and the sociocultural factors that influence the choices of people in seeking the best kind of treatment required for the injury. The findings reveal that despite the rise of modern medical practices, traditional bone setters still play a crucial role in providing affordable and accessible care.